TINJAUAN HUKUM ISLAM TERHADAP EFISIENSI PEMBAYARAN ZAKAT SECARA ONLINE DI BAZNAS - Baharuddin; Sohrah (Iqtishaduna: Jurnal Ilmiah Mahasiswa Hukum Ekonomi Syariah, 2022)
Islam is present in the midst of a society that is so unique that it presents various kinds. Zakat is one of the practices of the five pillars of Islam which is an absolute obligation for all Muslim communities as stated in the texts of the Qur'an and Al-Hadith. Therefore, everyone is encouraged to become muzakki, where each muzakki plays a role in overcoming poverty, meaning that hope is aimed at people who are able and to the poor themselves. The main problem in this study is how the Efficiency of Online Zakat Payments Judging from Islamic Law at the National Amil Zakat Agency Kab. soppeng. This type of research is a "qualitative" type of data, with the research approach used is a normative theological approach and socio-cultural approach. The results of the study show: 1.) Payment of zakat which is accessed online/via transfer at BAZNAS Kabupaten Soppeng through the BSI bank is inputted into the BAZNAS information management system which in full the funds that enter each year can print zakat income and expenditure. Each individual can access all forms of zakat transactions through the website or application that is paid via transfer. 2.) The efficiency of online zakat payments in terms of Islamic law is included in the category of darura as long as it runs according to sharia principles and there is no argument that prohibits it, the payment system is legal, so it can make it easier for muzakkih who do not have time to deliver their zakat to BAZNAS. However, the development of an online zakat system in Kabupaten. Soppeng still needs to be improved. Keywords: Efficiency, Islamic Law, Online Zakat.